Industrial training report: Intel Technology Sdn Bhd - Md Nasir, Farah Irdina (Universiti Teknologi MARA, Perlis, 2024)
This report details the comprehensive internship experience at Intel Corporation, highlighting key responsibilities, achievements, and personal growth. The internship duration is from February 19, 2024, to August 9, 2024, encompassing 25 weeks within Intel's Finance Department and under the Intercompany team. The orientation period included an introduction to Intel’s facilities and culture, equipping interns with necessary resources such as laptops and badges. The work schedule, predominantly remote, involved monthly on-site days and flexible office hours to accommodate global meetings. My primary responsibilities included validating Vietnam Account Payable open items to facilitate settlement processes, preparing Vietnam Withholding Tax working files, and uploading invoices into Eddar archival. Additionally, I handled various ad-hoc tasks such as match and clear operations, preparing reports, and assisting with high-level validations. One of my key achievements was the introduction of Python automation for the Vietnam IC account payable (AP) settlement categorization, which significantly improved efficiency and accuracy. Besides that, Intel also allowed me to develop expertise with financial software such as SAP, Blackline, and PowerBi Dax. The experience also improved my communication skills through the preparation of reports and presentations. Networking with finance professionals from different countries provided invaluable mentorship and career guidance, refining my professional aspirations and broadening my understanding of international finance. During my internship at Intel also I was able identify Intel's strategic position through a comprehensive SWOT analysis and outlines recommendations to enhance its market position.